2013
DOI: 10.1353/cpr.2013.0027
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cancer Screening in the Context of Unmet Mental Health Needs: A Participatory Pilot Study

Abstract: Background Cancer is the leading cause of preventable death in the Bronx, New York. Service providers in this mental health provider shortage area identified untreated mental illness as an important barrier to participation in cancer screening, a finding that supports existing literature. The Mental Health and Cancer (MHC) Connection partnership formed to investigate and address this issue. Objectives We sought to use an ecological framework to examine barriers and facilitators to obtaining mental health ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…11,26 At the system-level, there is also evidence of the prioritisation of more immediate health concerns in these individuals by primary care providers to the detriment of recommendations for preventative healthcare. 27,28 This is especially apposite given the highly influential role of primary care providers in encouraging participation in breast screening. 27,29 Furthermore, evidence from qualitative studies indicates that some individuals have reported feeling mistreated as a result of the stigma surrounding mental illness, and this lack of staff education and compassion negatively impacts a woman's likelihood of subsequent attendance.…”
Section: Discussionmentioning
confidence: 99%
“…11,26 At the system-level, there is also evidence of the prioritisation of more immediate health concerns in these individuals by primary care providers to the detriment of recommendations for preventative healthcare. 27,28 This is especially apposite given the highly influential role of primary care providers in encouraging participation in breast screening. 27,29 Furthermore, evidence from qualitative studies indicates that some individuals have reported feeling mistreated as a result of the stigma surrounding mental illness, and this lack of staff education and compassion negatively impacts a woman's likelihood of subsequent attendance.…”
Section: Discussionmentioning
confidence: 99%
“…The observed disparities in both cancer screening and mental health care among low-income and racial/ethnic women have resulted in an alarming public health situation. There is growing evidence that women who experience untreated mental health problems (e.g., depression) are less likely to participate in cancer screenings (22, 23). Lower participation in cancer screening results in cancer diagnoses at later stages of tumor growth and metastasis, contributing to higher morbidity and mortality rates (6).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Lower participation in cancer screening results in cancer diagnoses at later stages of tumor growth and metastasis, contributing to higher morbidity and mortality rates (6). Because this disparity widens among women from racial or ethnic minority groups (23), it is imperative to examine the intersectionality of sociodemographic factors on screening behaviors and depression treatment. That is, women who are both low-income and from racial/ethnic minorities may experience greater challenges related to cancer screening and depression treatment in additive and multiplicative ways, making them especially vulnerable to poor outcomes.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Given the observation that women who experience mental health problems such as depression are less likely to participate in preventive behaviors, including cancer screenings (Lin et al, 2019; Mitchell et al, 2014; Ross et al, 2020; Williams et al, 2013), a recognized need exists to address the cancer screening status among depressed women from lower-income backgrounds. A recent meta-analysis found that screening occurred significantly less frequently among individuals with mental illness compared with the general population (Solmi et al, 2020).…”
mentioning
confidence: 99%